(untitled) (Journal of Dentistry and Allied Science, 2024)
Replacing missing teeth, particularly in the anterior region, is a crucial aspect of dental practice. Fiber-reinforced composite resin bridges offer a conservative alternative to traditional fixed dental prostheses or implants. Fiberreinforced composite (FRC) resin bridges are gaining popularity as a minimally invasive, aesthetic, and costeffective solution for the replacement of missing teeth, particularly in the anterior region. This minimally invasive and reversible technique can be completed in just one visit. This case report details the clinical procedure, challenges, and outcomes associated with an FRC resin bridge for an anterior tooth replacement. Journal of Dentistry and Allied Science, Vol. 7 No 1: 45-48